Thalamic morphometric changes induced by first‐person action videogame training. (16th January 2019) - Momi, Davide; Smeralda, Carmelo; Sprugnoli, Giulia; Neri, Francesco; Rossi, Simone; Rossi, Alessandro; Di Lorenzo, Giorgio; Santarnecchi, Emiliano
Abstract: Cross‐sectional data suggest videogaming as promoting modifications in perceptual and cognitive skills of players, as well as inducing structural brain changes. However, whether such changes are both possible after a systematic gaming exposure, and last beyond the training period, is not known. Here, we originally quantified immediate and long‐lasting cognitive and morphometric impact of a systematic gaming experience on a first‐person shooter (FPS) game. Thirty‐five healthy participants, assigned to a videogaming and a control group, underwent a cognitive assessment and structural magnetic resonance imaging at baseline (T0), immediately post‐gaming (T1) and after  3 months (T2). Enhancements of cognitive performance were found on perceptual and attentional measures at both T1 and T2. Morphometric analysis revealed immediate structural changes involving bilateral medial and posterior thalamic nuclei, as well as bilateral superior temporal gyrus, right precentral gyrus, and left middle occipital gyrus. Notably, significant changes in pulvinar volume were still present at T2, while a voxel‐wise regression analysis also linked baseline pulvinar volume and individual changes in gaming performance. Present findings extend over the notion that videogame playing might impact cognitive and brain functioning in a beneficial way, originally showing long‐term brain structural changes even months after gaming practice. The involvement of posterior thalamic structures highlights a potential link between FPS games and thalamo‐cortical networks related to attention mechanisms and multisensory integration processing. Abstract : We investigated the impact of systematic, repeated gaming exposure to a first‐person shooter (FPS) action videogame in a sample of healthy subjects. Both cognitive and morphometric changes were found after training, including a significant long‐lasting change in posterior thalamus gray matter 3 months after exposure. The same thalamic region was identified as the best predictor of changes in gaming performance. Intensive practice with a FPS action videogame induces long‐lasting structural brain changes.